Pedagogía de la alimentación tradicional (2021)
This article is the result of research conducted at the Technical EducationalInstitution Plinio Mendoza Neira in the municipality of Toca, Boyacá (Colombia). The paper shows how the research process was with seventh grade students about ancestral foods: potatoes, ulluco, turnip, oca, squash and beans. In this process, participatory action research methodology was used with local knowledgeable people to describe the foods consumed and cultivated since preHispanic times. The text discusses the importance of relating academia, traditional knowledge and food as part of the motivational process of students in the development of commercial agriculture.